PENGARUH SIKAP DAN PERILAKU DALAM KELOMPOK PADA PT BANK SUMUT CABANG TARUTUNG - brico sitorus (Jurnal Media Informasi Manajemen, 2013)
The purpose of this study was to determine how much influence the attitude toward the behavior in PT Bank SUMUT Tarutung Branch. The population in this study were all employees of PT Bank SUMUT Tarutung Branch at front liner section which accounted for 36 employees. The sample in this study using saturated sampling consisting of 36 employees of PT Bank SUMUT Tarutung Branch. The data in this study conducted using primary data and secondary data. The primary data using questionnaires, which prior to the questionnaire distributed first tested the validity and reliability of the 20 employees at PT Bank SUMUT Balige Branch. Secondary data analysis using descriptive and quantitative analysis (simple linear regression analysis). The results showed that the relationship attitude positive and significant impact on the behavior of PT Bank SUMUT Tarutung Branch.Kata kunci: Sikap dan Perilaku Kelompok.Keywords: Attitudes and Behaviour Group.